Evaluasi Sistem Pengelolaan Rekam Medis Pasien Rawat Inap Study Kualitatif di RSKIA UMI KHASANAH - Tri Ariani; Eny Retna Ambarwati; Wiyadi (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Good management of medical records to support hospital services and useful if the informationcontained therein is complete and accurate. Medical record data is needed in the process of recordingand reporting routine hospitals. The purpose of this research is to treat and manage medical records ofinpatients at RSKIA Umi Khasanah Bantul. descriptive research with a qualitative approach. Researchsubjects Director, medical record personnel, midwives and doctors. Data collection using in-depthinterview techniques supported by documentation. Data analysis technique with reduction,presentation, conclusion. The results of the patient's medical research using a manual system. Medicalrecords are more than 2 x 24 hours because the medical record documents are not completely filled,the storage space is not sufficient, the SOP for medical records is not complete, the length of providingmedical records according to the law is <15 minutes, supervision medical records seen from theassessment indicators. The problem is that there is still a lack of medical record personnel, insufficientinfrastructure.Keywords: Evaluation, Management, Medical Records